Incorporating progesterone receptor expression into the PREDICT breast prognostic model - Grootes, Isabelle; Keeman, Renske; Blows, Fiona M.; Milne, Roger L.; Giles, Graham G.; Swerdlow, Anthony J.; Fasching, Peter A.; Abubakar, Mustapha; Andrulis, Irene L.; Anton-Culver, Hoda; Beckmann, Matthias; Blomqvist, Carl; et al. (European Journal of Cancer, 2022)
Background: Predict Breast (www.predict.nhs.uk) is an online prognostication and treatment benefit tool for early invasive breast cancer. The aim of this study was to incorporate the prognostic effect of progesterone receptor (PR) status into a new version of PREDICT and to compare its performance to the current version (2.2).
CRIS-Team WoS Importer:2022-11-25